Entrepreneurship in Information Technology as a Method for Improving Student Creativity in the Digital Economy - Rawat, Bhupesh; Maulidditya, Dwiki (Pandawan Sejahtera Indonesia, 2022)
In light of the digitalization era, the purpose of this study is to provide an overview of the significance of increasing self-innovation and creativity.The population of the research location at Universities is 115 sixth-semester IT entrepreneurship students. Using the sampling technique, 78 students make up the sample.This study employs descriptive analysis.The researcher used a structured interview technique in which several questions served as a guide for the interview.Structured and non-participant observation is the method of observation used.Observed aspects and structured observations are:The capacity of students to produce something novel and distinct (the capacity to produce the novel and distinct), their capacity for creative problem-solving, and their comprehension of IT business.While this was going on, non-participant observation was done by looking at blogs, Instagram, and other social media platforms that students used to complete assignments.According to the findings of the interviews and the observations that were made, respondents were aware of the current digital economy era, in which traditional methods are being replaced by modern ones made possible by technology.In addition, respondents are able to evaluate the competencies that are required to compete in the digital economy era as well as future opportunities and challenges.